Novel Self-Nanoemulsifying Drug Delivery System of Single Bulb Garlic: Stability, Toxicity, and Antiinflammation in 3T3-L1 Cells - Dewi Sekar Miasih; Yuslinda Annisa; Sri Rahayu Lestari; Hendra Susanto; Sunaryono (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2022)
Single bulb garlic (SBG) has the potential as an immunomodulator; however, it has low solubility and bioavailability. A lipid-based delivery system, that is, the self-nanoemulsifying drug delivery system (SNEDDS), offers a novel opportunity in drug delivery. SBG can be a suitable candidate for SNEDDS development. This research aims to describe the physical stability, toxicity test of the SNEDDS, and SNEDDS SBG potential as antiinflammation in 3T3-L1 cells. The SNEDDS is made with various ratios of concentrations of carrier oil, surfactants, and cosurfactants, namely, 0.50: 3.45: 0.96, and added with SBG extract (SBGE) of 20 mg/mL. The results of the response test of SNEDDS SBGE formulation indicate an average and standard deviation of emulsification time of 16.38±3.01 (second), pH 7.21±0.08, and transmittance of 98.40±0.23(%). The average nanoemulsion size is 14.333±0.416 nm, polydispersion index of 0.213±0.056, and zeta potential of -14.67±0.72 mV. The results of the physical stability test indicate no segregation, deposition, cracking, or creaming in all nanoemulsion samples and SNEDDS SBG. The MTT test in a dose of 62.5, 125, 250, 500, 100, 2000, and 4000 µg/mL suggests that the highest viability of the 3T3-L1 cells is at a dose of 2000 µg/mL, which is 97.83%±1.55%. Therefore, SNEDDS SBGE can be a potential candidate for oral preparation by increasing bioavailability and reducing toxicity in the 3T3-L1 cells. An antiinflammatory test on the TNF-???? and IL-1???? expressions influences the 3T3-L1 cells. the SNEDDS of SBGE has the potential to reduce the expression of TNF-???? and IL-1???? and increase IL-10 expression in the methylglyoxal-induced 3T3-L1 cells.